Rede transferencial e a clínica migrante: psicanálise em urgência social - Seincman, Pedro Magalhães (2017)
The present work investigates de psychoanalytic practice in contexts of social urgency, more specifically in the field of immigration. Based on the construction of two clinical experiences and their articulation with the psychoanalytical concept of transference, we intend to clarify the basis for the construction and management of transferential networks. We explain, on the one hand, how a network without a proper management can stiffen discursive positions and the speeches of those that are intended to care. On the other hand, the construction of a transferential network as well as the analysis of the silencing and of the discourses that take place in the relationship of all those involved in the field, can generate new modalities of social ties. We assume that a transferential network builds forms of resistances to the suffering produced in and by social practices. Thus, the network serves as a device for social intervention and, at the same time, as a discursive support so that the subject is not again forced to break with the bond or submit to the latter in fixed positions. It is in the discursive and political struggle of the network that the clinical case is constructed and that its directions are being produced. We emphasize the importance of taking into account the migrant process of the subject so that a new placement in the bond can occur, thus avoiding the repetition of social humiliation. We will no longer talk about the clinic of the migration, but that of the migration of the clinic, since the assembly and incidence of clinical devices take place in spaces and patterns that move between territories – geographic, social and psychic – and extrapolate the field of migration. The construction of new listening devices and the analytic process are mutually embodied according as new devices produce new discourses that, in turn, also generate new devices. However, without a network of protection, without a transferential network and a discursive network, one can succumb to the temptation of the single discourse that objectifies the subject as well as that of helplessness, thus hurting institutions and professionals